Does Experience Co-creation (XCC) Change Entrepreneurial Intention? - Firdaus Basbeth; Noorshela Che Nawi (International Journal of Business Studies, 2020)
Despite the global emphasis on the relevance and potential impacts of entrepreneurship has dramatically increased as potent economic force, entrepreneurship education has not significantly changed in two decades. Existing approaches to entrepreneurship education are focus is on teaching ‘about’ entrepreneur and what they do rather than teaching ‘for’ entrepreneurship. Drawing on the synthesis based on theory of planned behavior (TPB), we introduce Experience Co-creation as a new approach to teach entrepreneurship course based on the concept of experiential learning. The approach for the program was synthesized and adapted from Experience co-creation (XCC) theory used in tourism literature. This study develops a longitudinal framework of student’s intention after 3 months of the infusion of experiential learning. The result indicates that students’ intention is greater after the program than before the class started. This study fills a gap in entrepreneurship body of knowledge by providing evidence the teaching method moderates the relationship between perceived behavioral control and entrepreneurial intention. This study is an empirical study uses a SmartPLS3 with data taken from survey of 220 student in Strategic Entrepreneurship APT-2083 Class L4 & L5 Sem 2 2018/19. The result demonstrates that mean value of personal attitudes, subjective norms, perceived behavioral control and entrepreneurial intention are improved, and the relationship between perceived behavioral control and entrepreneurial intention improved significantly at the end of the course. The study suggest that university can gain highest entrepreneurial intention by introducing innovative method in teaching entrepreneurship.